Memahami pengaruh Self Efficacy, Locus of Control, dan Motivasi Intrinsik pada Kinerja Karyawan - Indriani, Linda; Indriastuti, Ariyani; Yustika, Putri (E-Prosiding Seminar Nasional Manajemen dan Akuntansi STIE Semarang (SNMAS), 2024)
This study aims to analyze the impact of Self-Efficacy, Locus of Control, and Intrinsic Motivation on Employee Performance at PT. Subah Spinning Mills, which has experienced a decline in production. Using a quantitative method with multiple linear regression analysis, the study found that all three independent variables significantly influence employee performance. The results indicate that improvements in Self-Efficacy, Locus of Control, and Intrinsic Motivation significantly enhance employee performance. The study concludes that developing these factors is crucial for improving employee performance and productivity.